The burden of iatrogenic obstetric fistulas in Sub-Saharan Africa: Systematic review and meta-analysis protocol - Imakando, M.M.; Maya, E.; Owiredu, D.; et al. (PLOS ONE, 2024)
Background Obstetric fistulas are abnormal open connection(s) between the vagina and the urinary tract or the rectum resulting from tragic injuries sustained by mothers during childbirth that lead to urine and/or faecal incontinence. Due to the rapidly growing middle class in sub-Saharan Africa (SSA) and the corresponding quest for hospital delivery and caesarean section, sur gery-related (iatrogenic) obstetric fistulas are on the rise. Worryingly, there is scanty data on surgery-related fistulas. This review aims to collate empirical evidence on the magnitude of iatrogenic obstetric fistulas in SSA, generate country-specific data and explore factors that influence obstetric surgery-related fistulas. Methods All relevant databases, PubMed, LILACS, CINAHL, SCOPUS and Google Scholar will be searched from 1st January 2000 to 31st March 2024 using search terms developed from the major concepts in the title without restrictions by language. The Cochrane Library, African Journals Online, Data Base of African Thesis and Dissertations Including Research (DATAD-R D Space) and preprint repositories will also be searched. Reference lists of relevant studies will be searched and experts in the field will be contacted for additional (unpublished) studies. The search output will be exported to Endnote where duplicate studies will be removed. The deduplicated studies will be exported to Rayyan where study screening and selection will be conducted. At least two authors will independently select studies, extract data and assess quality in the included studies using pretested tools. Disagreements between reviewers will be resolved through discussion. Data analysis will be performed with RevMan 5.4. Comparative binary outcomes will be reported as odds ratio (OR) or risk ratio (RR) and for continuous outcomes, mean difference and standard deviations (SDs) will be used. Non-comparative studies will be analysed as weighted proportions. Heterogeneity between studies will be assessed graphically and statistically, and where a significant level is detected, the random-effects model meta-analysis will be performed. All estimates will be reported with their 95% confidence intervals (CIs). Where data permit, we will conduct sub-group and sensitivity analyses to test the robustness of the estimates on key quality domains. The overall quality of the evidence will be assessed using GRADE (Grading of Recommendations Assessment, Development and Evaluation). Expected study outcomes This systematic review and meta-analysis uses rigorous methods and best practices to attempt to collate all empirical evidence and estimate country-specific proportions of iatrogenic (surgery-related) fistulas among obstetric fistula patients across countries in SSA. This review will explore context-specific variables, provide insights into their impact and relate them to the type and experience of personnel performing the obstetric procedures that lead to obstetric fistulas. The findings of the full review are expected to inform the development of national and regional Training Programs for Medical Officers, support the development of a consensus “minimum acceptable standard of care” and inform quality assurance standards for clinicians involved in the provision of surgical obstetric care.
Research Article
Keywords: iatrogenic obstetric fistulas; Sub-Saharan Africa; hospital